PELAKSANAAN PELATIHAN KERJA DI LEMBAGA PELATIHAN KERJA BALI AVIATION AND TOURISM CENTER (BATC) MENURUT UNDANG-UNDANG KETENAGAKERJAAN - Apriliani, Kadek (Fakultas Syariah Institut Agama Islam Negeri (IAIN) Pontianak, 2020)
This study aims to determine the job training implementation in the job training institutions Bali Aviation and Tourism Center (BATC) according to the Manpower Act. The research method used is empirical normative that is examining the implementation of the job training at the Bali Aviation and Tourism Center (BATC) job training institute to assess its compliance with the Labor Law. The results of the study revealed that the Bali Aviation and Tourism Center (BATC) as the provider of education and training in the field of aviation security personnel has received permission as a vocational training institution from the Office of Social Affairs and Labor of the City of Denpasar Province. The curriculum used has outlined the needs of industry and following labor law, specifically related to the development of work competencies that are implemented in the form of Daily Workers.